Alternative Public Personnel Management: Assessing The Efficacy of E-Catalog Based Office Services Procurement in Bolaang Mongondow Regency - I Dewa Agung Gede Krisna Waisaka; Nyoman Sri Subawa (Riviera Publishing, 2026)
The abolition of honorary workers through Law Number 20 of 2023 concerning the State Civil Apparatus has created new challenges for local governments in maintaining sustainable public administration services, particularly in managing non-ASN personnel who previously supported various operational functions. This study aimed to examine the implementation of E-Catalog-based procurement for general office services as an alternative strategy for non-ASN personnel management in the Regional Secretariat of Bolaang Mongondow Regency and to evaluate its organizational effectiveness. This research employed a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews with five key informants, direct observation, and document analysis, and were analyzed using the Miles and Huberman interactive model. The findings showed that E-Catalog-based procurement had been implemented through several stages, including needs planning, vendor selection, contract execution, and performance monitoring. Based on Richard M. Steers’ organizational effectiveness framework, the implementation contributed to organizational goal achievement, improved internal coordination, and strengthened institutional adaptation to national regulatory changes. However, several challenges remained, including limitations in network infrastructure, gaps in digital literacy among personnel, and the limited availability of qualified local service providers. Nevertheless, regulatory support, organizational leadership commitment, and national digital procurement infrastructure facilitated the sustainability of the system. This study concluded that E-Catalog-based procurement could serve as an alternative instrument for non-ASN personnel management by promoting transparency, accountability, and performance-oriented governance in the public sector.